Issues and developments on the consumer recovery construct - BELLACK, ALAN S. (Elsevier Italy, 2012)
The consumer recovery model has had increasing influence on mental health practices in the United States, Western Europe, and several other countries. However, adoption of the model has reflected political decisions rather than empirical evidence of the validity of the model or its value for treatment services. The recovery construct is poorly defined, and until recently there has been no reliable and valid measure with which to base a research program. We have developed an empirical measure that is well-suited for both research and clinical applications: the Maryland Assessment of Recovery in Serious Mental Ill-ness (MARS). We briefly describe the MARS and present preliminary data demonstrating that recovery is not a simple by-product of traditional outcome do-mains, but seems to be a distinct construct that may have important implications for understanding consumers with serious mental illness and for evaluating the outcome of treatment programs.